Gender Relations and Subjective Family Well-being among Farmer Families: a Comparative Study Between Uplands and Lowlands areas in West Java Province, Indonesia - Puspitawati, Herien; Faulkner, Paula; Sarma, Ma'mun; Herawati, Tin (Journal of Family Sciences, 2018)
The objectives of this study are described as follows: (1) To examine the conditions of social, economic and demographic characteristics of poor farmer families who live at uplands and lowlands areas, (2) to describe the social-cultural and agroecosystem conditions of poor farmer families who live at uplands and lowlands areas, (3) To explain type of gender relations of poor farmer families who live at uplands and lowlands areas, and (4) to analyze factors that influenced subjective family well-being of poor farmer families who live at uplands and lowlands areas. The chosen research sites were Nanggung Sub-district, Bogor District as an upland area, and West Teluk Jambe Sub-district, Karawang District, West Java Province as a lowland area. The total of 189 farmer families was used for this study (n= 90 in uplands district areas, and n= 99 in lowlands district areas). It was found that the conditions of social-cultural and agroecosystem differ between upland and lowland areas. In general, both upland and lowland areas gender roles on farming activities, in terms of access and control to agricultural resources, were dominated by men. Family well-being was directly influenced by higher education of husband and wife, indirectly influenced by less economic pressure of the family, directly influenced by higher gender relations between husband and wife, and directly influenced by less or higher external support. Thus, wealthy farmer families were the family that had educated husband and wife, less economic pressures, equal gender relations and partnerships, and less or more receive external supports. It is recommended that the next study should add variables of family coping strategies related to family economic pressure and gender roles between husband and wife.